2016
DOI: 10.1039/c5cp07758c
|View full text |Cite
|
Sign up to set email alerts
|

Optical and photophysical properties of anisole- and cyanobenzene-substituted perylene diimides

Abstract: One- and two-photon absorption cross-sections and spectra and the photophysical properties of eight perylenetetracarboxy-3,4:9,10-diimide (PDI) derivatives are reported and analyzed. The investigated compounds are characterized by direct binding of the phenyl rings of the substituents to the bay positions of the perylene core. They have been designed to test the effects of differences in the electronic nature - electron donating (anisole) or accepting (cyanobenzene) - and binding topology (cis or trans, meta o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…The latter effect is generally attributed to an out‐of‐plane distortion of the perylene ring system because of the sterically encumbered substituent groups 65, 66. The overall bathochromic shift of the maximum absorption wavelength is due to the π‐donating effect of the oxygen substituents on the perylene ring system 52. The fluorescence spectra of 1,12‐bay‐substituted PDIs are a mirror image of their corresponding absorption spectra (Figure 3 a), including the loss of vibronic fine structure accompanied by a relatively large Stokes shift as compared with PDI 1 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The latter effect is generally attributed to an out‐of‐plane distortion of the perylene ring system because of the sterically encumbered substituent groups 65, 66. The overall bathochromic shift of the maximum absorption wavelength is due to the π‐donating effect of the oxygen substituents on the perylene ring system 52. The fluorescence spectra of 1,12‐bay‐substituted PDIs are a mirror image of their corresponding absorption spectra (Figure 3 a), including the loss of vibronic fine structure accompanied by a relatively large Stokes shift as compared with PDI 1 .…”
Section: Resultsmentioning
confidence: 97%
“…[65,66] The overall bathochromic shift of the maximum absorption wavelength is due to the p-donating effect of the oxygen substituents on the perylener ing system. [52] The fluorescence spectra of 1,12-bay-substituted PDIs are am irror image of their corresponding absorption spectra (Figure 3a), Figure 2. A) Expansion of the aromatic region of the 2D 1 H, 13 CHMBCs pectrum of PDI 3.The inset showsthe molecular structure of PDI 3 with the assigned protons and carbons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These molecules have 2,6diisopropylphenyl groups at the imide positions and the derivative with four p-methoxyphenyl as bay substituents has a cross section of 180 GM at 850 nm, one order of magnitude greater respect to the reference derivative with no substituents in the bay positions. 46 It was also shown that tetrasubstitution causes twisting of the perylene core because of the steric hindrance between the phenyl rings connected at the bay positions. Another way of bay substitution involves the use of an ether linker between the perylene core and the -delocalized groups.…”
Section: Introductionmentioning
confidence: 99%